Uncertainty, bounded rationality and post-Keynesian Macroeconomics - Finn Olesen (Intervention. European Journal of Economics and Economic Policies, 2010)
As a core element in mainstream neoclassical theory we assume that economic agents behave rationally. They have full information about everything of economic relevance at present, as well as concerning the future. They either maximize their profit or their utility. Is the model of the rational economic man realistic and a useful concept? According to post-Keynesians and the school of bounded rationality (e.g. the works of Herbert Simon and others) the answer to this question is No. In this paper we discuss some aspects of bounded rationality and the position taken by Keynes and by the post-Keynesians who argued that actual behaviour is restricted and less than perfect due to the existence of fundamental uncertainty as pointed out by Keynes in his General Theory. Therefore, the macroeconomic system should be seen as an open, changeable and path-dependent system.
Keywords: B22; B41; E12; 330; uncertainty; bounded rationality; post-Keynesian economics